Interior design inspirations - Reschke, Cynthia (Barcelona, Spain : LOFT Publications, 2009)
This book is a richly illustrated exploration of residential interior design from around the world, showing the multifarious ways in which occupants and interior designers meet the challenge of designing residential space
1. Introduction -- 2. Entrances & hallways -- 3. Kitchens -- 4. Dining rooms -- 5. Bedrooms -- 6. Bathrooms -- 7. Home offices -- 8. Terraces -- 9. Garages
"FRG."
Includes text in German, English, Spanish, Italian, and French
Keywords: Interior decoration